JIT single machine scheduling problem with periodic preventive maintenance - Mohammadreza Shahriari; Naghi Shoja; Amir Ebrahimi Zade; Sasan Barak; Mani Sharifi (Journal of Industrial Engineering International, 2016)
This article investigates a JIT single machine scheduling problem with a periodic preventive maintenance. Also to maintain the quality of the products, there is a limitation on the maximum number of allowable jobs in each period. The proposed bi-objective mixed integer model minimizes total earliness-tardiness and makespan simultaneously. Due to the computational complexity of the problem, multi-objective particle swarm optimization (MOPSO) algorithm is implemented. Also, as well as MOPSO, two other optimization algorithms are used for comparing the results. Eventually, Taguchi method with metrics analysis is presented to tune the algorithms' parameters and a multiple criterion decision making technique based on the technique for order of preference by similarity to ideal solution is applied to choose the best algorithm. Comparison results confirmed the supremacy of MOPSO to the other algorithms.
Keywords: 650; Scheduling; Single machine; Periodic maintenance; Total earliness-tardiness; Multi-objective optimization; MCDM